2013
DOI: 10.3390/md11051718
|View full text |Cite
|
Sign up to set email alerts
|

Polyketides from a Marine-Derived Fungus Xylariaceae sp.

Abstract: Eighteen polyketides (1–18) including six citrinin derivatives, two phenol derivatives, one cyclopentenone, two naphthol derivatives, and seven tetralone derivatives were isolated from the culture broth of a marine-derived fungal strain Xylariaceae sp. SCSGAF0086. Five of these compounds (1, 2, 8, 9, and 10) were new, and their structures were determined by spectroscopic methods. Compounds 4, 6, 7, and 17 showed enzyme-inhibitory activities towards several tested enzymes, and 6 and 7 showed strong antifouling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…citrinum OUCMDZ4136 in the SWS medium containing 0.5% NaF. By comparison of NMR and specific rotation data with those reported, their structures were identified as 2,4-dihydroxy-3,5,6-trimethylbenzoic acid ( 1 )1314, citreorosein ( 2 )1516, pinselin ( 3 )17, citrinin ( 4 )181920, dihydrocitrinone ( 5 )2122, pennicitrinone A ( 6 )2324 and quinolactacin A1 ( 7 )25, respectively (Fig. 9).…”
Section: Resultsmentioning
confidence: 94%
“…citrinum OUCMDZ4136 in the SWS medium containing 0.5% NaF. By comparison of NMR and specific rotation data with those reported, their structures were identified as 2,4-dihydroxy-3,5,6-trimethylbenzoic acid ( 1 )1314, citreorosein ( 2 )1516, pinselin ( 3 )17, citrinin ( 4 )181920, dihydrocitrinone ( 5 )2122, pennicitrinone A ( 6 )2324 and quinolactacin A1 ( 7 )25, respectively (Fig. 9).…”
Section: Resultsmentioning
confidence: 94%
“…The relative configuration of 2 was assigned on the basis of the NOESY correlations of H-1 and H-4 with H-11 as well as H-3 with H-12. The absolute configuration of 2 was determined by comparison of its specific optical rotation value ( (Nong et al, 2013), which suggested that the absolute configuration of 2 was also 1S,3R,4S. So, the structure of 2 was elucidated as (1S,3R,4S)-1-(4 0 -hydroxylphenyl)-3,4-dihydro-3,4,5-trimethyl-1H-2-benzopyran-6,8-diol.…”
Section: Resultsmentioning
confidence: 99%
“…Nong et al isolated two natural antifouling products (dicitrinin A and phenol A acid) from the marine gorgonian-derived fungal strain Xylariaceae sp. SCSGAF0086 [ 41 ]. Dicitrinin A shows enzymatic inhibition of Src homology 2 domain-containing phosphotyrosine phosphatase and inosine monophosphate dehydrogenase, while phenol A acid inhibits cathepsin B.…”
Section: Antifouling Compounds With Proposed Specific Targetsmentioning
confidence: 99%
“…Dicitrinin A shows enzymatic inhibition of Src homology 2 domain-containing phosphotyrosine phosphatase and inosine monophosphate dehydrogenase, while phenol A acid inhibits cathepsin B. However, the existence of a link between enzyme inhibition and settlement-deterrence of the bryozoan Bugula neritina was not clarified for dicitrinin A and phenol A acid [ 41 ].…”
Section: Antifouling Compounds With Proposed Specific Targetsmentioning
confidence: 99%